Dampak Globalisasi Terhadap Identitas Budaya dan Konsumerisme di Indonesia - Purnomo, Muhammad Aditya; Syuryansyah, Syuryansyah (Syntax Literate, 2025)
Globalization has significantly influenced various aspects of Indonesian society, particularly through innovations in information and communication technology. This study aims to analyze the impact of globalization on cultural identity and consumerism in Indonesia. Using a qualitative approach with a descriptive method, the research collected data through document analysis, participatory observations, and documentation from relevant sources. The study was conducted in major cities such as Jakarta, Bandung, and Surabaya to explore global cultural phenomena, including Japanese culture (Cosplay) and South Korean culture (K-Pop). The findings reveal that the development of information technology, such as the internet and social media, facilitates access to foreign products and cultures. While this has positive effects, such as the convenience of shopping through e-commerce platforms, it also poses challenges, including the gradual erosion of local culture due to the influence of foreign phenomena like Cosplay from Japan and the K-Pop craze from South Korea. These phenomena highlight the challenges Indonesian society faces in preserving local cultural identity amidst the strong currents of globalization.